1998
DOI: 10.1046/j.1471-4159.1998.71062239.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression of Cloned Human Galanin Receptors GALR2 and GALR3

Abstract: Abstract:Galanin is a 29-or 30-amino acid peptide with wide-ranging effects on hormone release, feeding behavior, smooth muscle contractility, and somatosensory neuronal function. Three distinct galanin receptor (GALR) subtypes, designated GALR1, 2, and 3, have been cloned from the rat. We report here the cloning of the human GALR2 and GALR3 genes, an initial characterization of their pharmacology with respect to radioligand binding and signal transduction pathways, and a profile of their expression in brain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 26 publications
10
129
0
Order By: Relevance
“…Galanin decreases presynaptic DA release in striatal slices (Tsuda et al, 1998) and one possible explanation for the heightened sensitivity of GKO mice to morphine-induced locomotion and CPP is that knockout of the peptide may result in hyperactivation of DA signaling following opiate administration. Whereas mRNA levels for galanin receptors are low in the NAc, galanin receptor binding is quite prominent (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), indicating that localization of galanin receptors on DA terminals might regulate DA release. Galanin is also known to be a potent inhibitory modulator of basal acetylcholine (ACh) release in the striatum (Antoniou et al, 1997) and it has been demonstrated that M1-muscarinic receptors and high-affinity nicotinic receptors regulate the secondary rewarding effects of cues paired with a primary reinforcer such as morphine (Brunzell et al, 2006;Carrigan and Dykstra, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galanin decreases presynaptic DA release in striatal slices (Tsuda et al, 1998) and one possible explanation for the heightened sensitivity of GKO mice to morphine-induced locomotion and CPP is that knockout of the peptide may result in hyperactivation of DA signaling following opiate administration. Whereas mRNA levels for galanin receptors are low in the NAc, galanin receptor binding is quite prominent (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), indicating that localization of galanin receptors on DA terminals might regulate DA release. Galanin is also known to be a potent inhibitory modulator of basal acetylcholine (ACh) release in the striatum (Antoniou et al, 1997) and it has been demonstrated that M1-muscarinic receptors and high-affinity nicotinic receptors regulate the secondary rewarding effects of cues paired with a primary reinforcer such as morphine (Brunzell et al, 2006;Carrigan and Dykstra, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All three galanin receptor subtypes, as well as significant galanin binding, are found in the ventral tegmental area (VTA), amygdala, nucleus accumbens (NAc), cingulate cortex, and locus coeruleus (LC) (Burgevin et al, 1995;Gustafson et al, 1996;Hawes and Picciotto, 2004;Kolakowski et al, 1998;Waters and Krause, 2000), areas of the brain known to contribute to drug addiction and reward. Galanin also regulates the levels and release of a number of neurotransmitters, including dopamine, acetylcholine, and norepinephrine (Pieribone et al, 1995;Tsuda et al, 1998;Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The biological activities of Gal-R1 and -R3 receptors are mediated by Gi/G0 G-proteins, leading to the inhibition of adenylate cyclase (Kolakowski et al, 1998). In our study, their associated signalling pathways may have played a role in the poorly differentiated NT (or NB).…”
Section: Discussionmentioning
confidence: 65%
“…Sequences were complementary to the nucleotides 60 -107, 139 -186 encoding for human preprogalanin (McKnight et al, 1992), to nucleotides 6 -53, 984 -1031 of the mRNA encoding the human Gal-R1 (HabertOrtoli et al, 1994), to nucleotides 91 -138, 1001 -1048 of the mRNA encoding the human Gal-R2 (Kolakowski et al, 1998) and to nucleotides 41 -88, 921 -968 of the mRNA encoding the human Gal-R3 (Kolakowski et al, 1998).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation